Unveiling the Theoretical Foundations and Practical Applications of Key Conceptual Research Models in Marketing, Management, Technology, and Information Systems: A Systematic Review - Bhuiyan, Mohammad Rakibul Islam; Islam, Zahidul; Faraji, Mahfujur Rahman; Bandapadya, Koushik; Abedin, Md Zainal; Ali, Md. Hazrat; Amin, Al- (Journal of Posthumanism, 2025)
This systematic review aims to uncover the theoretical foundations and practical applications of prominent research models within the domains of marketing, management, technology, and information systems. The study examines a comprehensive set of 143 articles, from which 106 peer-reviewed sources were meticulously selected for analysis. Utilizing both qualitative and quantitative approaches, the review integrates findings from systematic reviews, meta-reviews, and meta-analyses to provide a nuanced understanding of various theoretical frameworks. The research focuses on evaluating key models including the Theory of Planned Behavior (TPB), AIDA Model, System Approach, Contingency Approach, DeLone and McLean IS Success Model, Unified Theory of Acceptance and Use of Technology (UTAUT), and the Technology Acceptance Model (TAM) along with its extensions (TAM 2). By addressing gaps, inconsistencies, and conflicting findings in these models, the review offers insights from social, technological, and managerial perspectives. The analysis highlights the strengths and limitations of each model, identifies research gaps, and suggests future research directions to enhance theoretical and practical applications. The findings underscore the importance of integrating cross-disciplinary insights and conducting context-sensitive studies to improve the applicability and effectiveness of these frameworks. This review not only contributes to the academic understanding of these models but also provides actionable recommendations for practitioners in marketing, management, and information systems.